Influences on International Student Choice of Study Destination: Evidence from the United States - Nicholls, Sarah (Journal of International Students, 2018)
Competition to attract international students continues to grow and understanding the factors that influence study destination choice is critical to the marketing efforts of nations, states, and institutions. This surveybased study of international students at Michigan State University demonstrates that they appear to choose the country in which to study, and/or the specific school, with less regard for school location. The most critical influences on their choices were expected quality of education, reputation/ranking of the university and individual departments/programs, safety/security, and cost/affordability. Differences in relative importance by nationality, gender, and level of education sought were also identified. Implications of these findings, for the marketing, promotion, and recruitment efforts of universities and national/regional economic development agencies, are discussed.